The thing on the doorstep - Gliserman , Tom; Hansen, Mary Jane; Bunce, David; Lovecraft, H. P. (Howard Phillips), 1890-1937.; Handsome Spyder, Inc.; Leomark Studios (Firm) ([Saratoga, NY] : Handsome Spyder, Inc., 2014)
A new psychological horror film based on the story by H.P. Lovecraft. Daniel Upton's relationship with his friend Edward Derby is abruptly changed after Edward becomes romantically involved with enigmatic hypnotist, Asenath Waite. As Edward's behavior becomes more erratic and events unexplainable, Daniel investigates. Is it madness...or something far more terrifying? "It is true that I have just sent six bullets through the head of my best friend, and yet I hope to show by this statement that I am not his murderer."
Originally released as a motion picture in 2014.
David Bunce, Susan Cicarelli-Caputo, Rob Dalton, Ron Komora, Mary Jane Hansen.
Cinematographer and editor, Tom Gliserman ; music, Will Severin.
In English with English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed July 8, 2016).
Keywords: Horror films; Thrillers (Motion pictures); Feature films; Internet videos; Streaming video